Identification of Compounds that Selectively Stabilize Specific G‐Quadruplex Structures by Using a Thioflavin T‐Displacement Assay as a Tool. Issue 52 (15th November 2016) - Jamroskovic, Jan; Livendahl, Madeleine; Eriksson, Jonas; Chorell, Erik; Sabouri, Nasim
Abstract: Small molecules are used in the G‐quadruplex (G4) research field in vivo and in vitro, and there are increasing demands for ligands that selectively stabilize different G4 structures. Thioflavin T (ThT) emits an enhanced fluorescence signal when binding to G4 structures. Herein, we show that ThT can be competitively displaced by the binding of small molecules to G4 structures and develop a ThT‐displacement high‐throughput screening assay to find novel and selective G4‐binding compounds. We screened approximately 28 000 compounds by using three different G4 structures and identified eight novel G4 binders. Analysis of the structural conformation and stability of the G4 structures in presence of these compounds demonstrated that the four compounds enhance the thermal stabilization of the structures without affecting their structural conformation. In addition, all four compounds also increased the G4‐structure block of DNA synthesis by Taq DNA polymerase. Also, two of these compounds showed selectivity between certain Schizosaccharomyces pombe G4 structures, thus suggesting that these compounds or their analogues can be used as selective tools for G4 DNA studies. Abstract : A straightforward and cost‐effective high‐throughput screen based on a thioflavin T‐displacement assay allowed the screening of three different G‐quadruplex (G4) structures (see figure). As a result, new potent G4 DNA‐binding compounds were identified that can bind and selectively stabilize G4 DNA molecules folded into different structures. These compounds facilitate studies of the biological functions of G4 structures and are important for therapeutics.